Bilateral ureteropelvic junction obstruction: Factors guiding management - Mandelia, Ankur; Yadav, Rajnikant; Dhoat, Navdeep Singh (Indian Journal of Child Health, 2018)
Background: The management of prenatally detected hydronephrosis due to bilateral ureteropelvic junction obstruction (UPJO) remains controversial. No definite recommendations exist regarding management, and many authors recommend unilateral or bilateral pyeloplasty. Objective: This study was conducted to evaluate the clinical outcome of patients with bilateral UPJO treated at a tertiary care hospital. Materials and Methods: This descriptive study was performed in the Department of Pediatric Surgery, Lucknow. All patients with prenatally diagnosed bilateral hydronephrosis and postnatal diagnosis of bilateral UPJO, who underwent initial unilateral pyeloplasty, were prospectively evaluated and were included in the study. The outcome of contralateral hydronephrosis was assessed as resolution or surgery. Results: A total of 16 patients underwent initial unilateral pyeloplasty and met the inclusion criteria (mean age: 2.6 months). Of all 16 patients, 12 (75%) had resolution and 4 (25%) patients required additional contralateral pyeloplasty during the follow-up. The mean follow-up period was 18 months (range 9–36 months) and the mean anteroposterior pelvic diameter and pelvis-to-cortex (P/C) were significantly different among the groups (p